Rare earth elements : processing, catalytic applications and environmental impact - Basu, Basudeb; Banerjee, Bubun (Walter de Gruyter GmbH, 2023)
Over the years, the uses and applications of rare earth elements (REEs) diversified in various fields such as catalysis, production of magnets, glasses, alloys, and electronics. This book consists of fifteen chapters, which present recent advances and outlook on REEs and their oxides/salts in catalytic organic transformations, biomedical applications, bioremediation and environmental impacts.